Climate Action Innovation Hub - Trautman, Sabrina; Chevallier, Romy; Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The African Union Commission (AUC) launched the inaugural strategic Climate Action Innovation Hub (the Innovation Hub) at the Africa Climate Summit (ACS). The Innovation Hub, hosted at the African Union House between the 4th – 6th September, was a unique event to profile Africa’s young people and women engaged in climate action through innovation. The Innovation Hub provided an opportunity to showcase a diverse range of the bold, innovative climate actions taking place across the continent that align with the specific ambitions and goals of the recently adopted African Union Climate Change and Resilient Development Strategy and Action Plan (2022-2032) the AU Climate Strategy). This is Africa’s first ever climate change action plan and strategy that details specific suggested actions that the continent needs to undertake to respond to climate change.